2009
DOI: 10.1039/b821437a
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Raman spectroscopy with a fast intensified CCD camera for depth analysis of diffusely scattering media

Abstract: A spectroscopic depth profiling approach is demonstrated for layers of non-transparent, diffusely scattering materials. The technique is based on the temporal discrimination between Raman photons emitted from the surface and Raman photons originating from a deeper layer. Excitation was carried out with a frequency-doubled, 3 ps Ti:sapphire laser system (398 nm; 76 MHz repetition rate). Time-resolved detection was carried out with an intensified CCD camera that can be gated with a 250 ps gate width. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…It has been used for a wide variety of applications including cancer diagnosis [1,2], the detection of hazardous materials [3], and industrial quality control. Raman spectroscopy has previously been carried out in turbid media [4,5]; however, the effect elastic scattering has on the process has yet to be investigated. In other words, is there a way to use elastic scattering to optimize Raman generation?…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for a wide variety of applications including cancer diagnosis [1,2], the detection of hazardous materials [3], and industrial quality control. Raman spectroscopy has previously been carried out in turbid media [4,5]; however, the effect elastic scattering has on the process has yet to be investigated. In other words, is there a way to use elastic scattering to optimize Raman generation?…”
Section: Introductionmentioning
confidence: 99%
“…The concept was developed from earlier temporal-domain Raman counterparts [5,[17][18][19][20] which utilised time-correlated single-photon counting [17] or picosecond Raman Kerr gating (the latter developed originally for fluorescence rejection from Raman spectra [4,[21][22][23]. A CCD gated method has also been demonstrated recently for subsurface probing [24] and its potential for combining with SORS has been demonstrated [25]. Although beneficial in some situations the temporal concepts are restricted by higher instrumental complexity and cost.…”
Section: Sorsmentioning
confidence: 99%
“…The use of a short detector gate allows selective collection of Raman photons from a certain depth within the sample and eliminates a considerable amount of fluorescent background from the surface as well as from the bulk. 17,19,20 Combinations of SERS, SORS, and TRRS are also possible. Previous work has shown that a slight improvement of the selectivity for photons from the bulk versus the surface can be achieved by combining TR detection with a SORS excitation geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS), spatially offset Raman spectroscopy (SORS), and time-resolved Raman spectroscopy (TRRS) are all advanced Raman techniques that have been introduced, in part, to overcome the problem of fluorescence interference in a variety of applications. [14][15][16][17][18][19][20] Through signal enhancement and selectivity for material in the bulk versus the surface, these methods could also help in studying the inside of catalyst extrudates in more detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation